DEFENSE MECHANISM OF SAYURI'S PROBLEM IN ROB MARSHALL'S MEMOIRS OF A GEISHA MOVIE (2005): A PSYCHOANALYTIC APPROACH - NILASARI, NUNIK (2011)
The research is aimed to analyze defense mechanism in a movie with the title Memoirs of a Geisha (2005) with psychoanalytic approach. There are two objectives: the first is to analyze the movie in term of structural elements, and the second is to analyze defense mechanism of the major character of the movie based on Psychoanalytic Approach. The writer employs the qualitative research method. There are two kinds of data namely the primary data and the secondary data. The primary data are the movie and the secondary data sources are some books, internet, and articles related to the subject. The technique of data collection in this research is library research and the technique of the data analysis is descriptive technique. Based on the analysis, the writer draws some conclusion as follows. First, the researcher concludes that defense mechanism rises because of drives from system personality. When id wants to satisfy soon, superego must consider with moral it will arise conflict in the personality. Then if the conflict cannot be solved, it raises the defense mechanism and the person will be suffering.